The virtual as a means of critical transformation of the real - Spitz, Rejane (2021)
Based on the notion of the virtual as a means of critical transformation of the real, in this article we discuss concepts related to immersiveness, addressing aspects of sense of presence, interactivity, collaboration, motivation, emotion and engagement. From the analysis of a set of original and visionary immersion works, we discuss the contribution of Art to the field of Virtual Reality. The Electronic Art Laboratory (PUC-Rio), its work methodology, results and academic contribution are described. Then, we present the project “VRestaurant: food for thought”, an immersive, synesthetic, gastronomic and collaborative artistic in-stallation, whose objective is to discuss the challenges we face today in relation to the production and consumption of food, on a global scale. Will we be able to feed 10 billion people on the planet in a healthy and sustainable way by 2050? In conclusion, we make considerations about the role of Electronic Art in projects that promote awareness, engagement and social changes.